Pengaruh Implementasi Pelatihan Dasar Calon Pegawai Negeri Sipil terhadap Pengembangan Kompetensi di Rumah Sakit Umum Sofifi - Taufik Karim (Jurnal Kewidyaiswaraan, 2020)
This study aims to find first, knowing respondents’ perceptions of the implementation of BasicTraining for Prospective Civil Servants, secondly knowing the results of competency development after respondents take the Basic Training for Prospective Civil Servants, and thirdly knowing the effect of the implementation of Basic Civil Servant Candidate Training on competency development. The research method used in this study is a quantitative method. The sample used in the study were all 92 Basic Training alumni at Sofifi General Hospital. Data collection techniques used in the study were the distribution of questionnaires and interviews. The data analysis technique was performed using the Simple Regression method. The results of the study note that, firstly in general the implementation of Basic Training for Prospective Civil Servants in the Human Development Agency of North Maluku Province has run well or is in accordance with National Institute of Public Administration The Republic of Indonesia Regulation No. 12 of 2018 concerning Basic Training for Prospective Civil Servants. Second, the training output has been effective in making a real contribution in increasing the competency of Sofifi General Hospital employees in improving organizational performance. While the third effect of basic training of prospective civil servants on competency development has a contribution of 24.5% while the rest is influenced by other variables.